2015
DOI: 10.1210/jc.2015-2493
|View full text |Cite
|
Sign up to set email alerts
|

Crooke's Changes In Cushing's Syndrome Depends on Degree of Hypercortisolism and Individual Susceptibility

Abstract: Crooke's changes occur in 75-80% of patients with CS, and depend on the degree of hypercortisolism and individual variability. Almost all patients with UFC at least 4-fold the upper limit of normal have them, whereas with less severe hypercortisolism the expression of Crooke's changes varies from person to person.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(21 citation statements)
references
References 6 publications
1
19
1
Order By: Relevance
“…These changes are known as Crooke’s hyaline changes, and their identification is of paramount importance. The presence of these changes is associated with the degree of hypercortisolism and individual susceptibility to it [300]. These changes involve the massive accumulation of perinuclear cytokeratin under the effect of excessive glucocorticoid levels.…”
Section: Pathological Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…These changes are known as Crooke’s hyaline changes, and their identification is of paramount importance. The presence of these changes is associated with the degree of hypercortisolism and individual susceptibility to it [300]. These changes involve the massive accumulation of perinuclear cytokeratin under the effect of excessive glucocorticoid levels.…”
Section: Pathological Characteristicsmentioning
confidence: 99%
“…Consequently, their presence can be used to confirm CS in patients in whom no signs of CS are noted during the surgical exploration of the pituitary. Conversely, approximately 20% of the patients with ACTH-positive pituitary tumor at surgery did not exhibit Crooke’s changes, thus, the absence of Crooke’s changes does not always establish the absence of CS [299,300]. Non-neoplastic increase in the number of adenohypophyseal corticotrophs, called corticotroph hyperplasia, in which the reticulin framework is intact but expanded, may be due to the reduced negative feedback effect of glucocorticoids or increased exposure to CRH.…”
Section: Pathological Characteristicsmentioning
confidence: 99%
“…These changes are histological changes known as Crooke's changes. 76 The presence of these changes is associated with the degree of hypercortisolism and individual susceptibility to them. The changes are never present in the absence of hypercortisolism.…”
Section: Pathologic Findingsmentioning
confidence: 99%
“…In a recent study, it was shown that depending on the degree of hypercortisolism, densely/sparsely corticotroph tumors show focal Crooke’s changes 67 . This suggests that Crooke’s cell adenomas have no specific genetic/epigenetic background but derive from densely/sparsely CAs at a high hypercortisolemic state.…”
Section: Progression Of Corticotroph Adenomasmentioning
confidence: 99%